2017
DOI: 10.1055/s-0037-1606339
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Duration Impacts Venous Thromboembolism Risk in Microsurgical Breast Reconstruction

Abstract: Risk, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 56 publications
(54 reference statements)
0
20
0
2
Order By: Relevance
“…Similarly, operative time has been shown in various papers to be associated with adverse outcomes in free flap breast reconstruction. 30,31 In a landmark paper by Kwok et al, the NSQIP database was queried for patients undergoing free flap breast reconstruction. The authors concluded that prolonged operative time is associated with an increased probability of flap failure.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, operative time has been shown in various papers to be associated with adverse outcomes in free flap breast reconstruction. 30,31 In a landmark paper by Kwok et al, the NSQIP database was queried for patients undergoing free flap breast reconstruction. The authors concluded that prolonged operative time is associated with an increased probability of flap failure.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged operative time has more frequently been mentioned as an important factor for complications, especially in free flap breast reconstruction. [19][20][21] To further specify our analysis, overall complication rate was analyzed using the same logistic regression model on separate datasets for each type of procedure. In our logistic regression model, cases with missing data were excluded of analysis by case-wise deletion.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Risk factors for DVT include prolonged surgery, positive BRCA status, greater age, high BMI, concurrent tamoxifen therapy, and delayed mobilization. 56,57 Practices in DVT prophylaxis vary greatly among reconstructive breast surgeons, and most report noncompliance with American College of Chest Physicians (ACCP) guidelines. 58 Lowmolecular weight heparin (LMWH) is often the prophylactic medication of choice and given daily to all patients throughout the course of admission.…”
Section: Complicationsmentioning
confidence: 99%